Conservation of melanistic girdled lizards in the Saldanha area and reference to background colour-matching and sexual dimorphism - Cordes, Imke Gesa (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc.) -- University of Stellenbosch, 1995.